Kontribusi Sektor Pertanian berdasarkan Keunggulan Wilayah di Kabupaten Bangka - Tirani, Tirani; Pranoto, Yudi Sapta; Moelyo, Haryono (Caraka Tani: Journal of Sustainable Agriculture, 2018)
This study aims to describe the contribution of agriculture sector based on superior sub-sector (base) in Bangka Regency. This research was conducted in November 2016 until May 2017 in Bangka Regency. This research uses survey method. The research uses secondary data which collected from several agencies in Bangka District. The method of analysis is Location Quotient (LQ). The result of research shows that Bakam District has one base sub-sector that is annual estate sub-sector; Belinyu District has two basic sub-sectors, namely livestock sub-sector and fishery sub-sector; Merawang District has three sub sectors namely horticultural crops sub-sector, fishery sub-sector, and livestock sub-sector; West Mendo District has two basic sub-sectors, namely food crops sub-sector and annual crop sub-sector and other horticulture sub-sector; Pemali District has two sub-sectors, namely food crops and annual plantation sub-sector; Puding Besar District has one sub-sector that is the annual plantation sub-sector; Riau Silip District has two sub-sectors of base, namely food crop sub-sector and plantation sub-sector yearly; and Sungailiat District has three sub sectors namely horticulture and annual crops sub sector, fishery sub-sector, and livestock sub-sector.